Assessing the Person–Job Fit in the European Union Aviation Industries Using a Competency Gap Assessment Framework. Issue 1 (January 2014) - Reis, Vasco; Macário, Rosário
Over the past few decades, the European Union's (EU's) aviation industries have experienced a dwindling of their long-standing capacity to attract and retain the most promising students. A misalignment or gap between the competencies needed at work and those earned at school is just one of the several potential causes already identified. Such a gap may be eroding the person–job fit, namely, the difference between the perceived applicant–job fit and the actual employee–job fit, and thus contributing to making these industries less attractive. The purpose of the research was to evaluate the person–job fit along two dimensions: perceived applicant–job and actual employee–job fit in the EU aviation sector. Competency was the component used to operationalize the measurement of the person–job fit. A competency gap assessment framework estimated the gaps between the competencies for adequately performing the job tasks and those acquired by higher education students. A total of 88 competencies, divided into four domains of activity (airlines, airports, air navigation service providers, and manufacturers), were taken into consideration. The methodological approach included two large-scale surveys. The results evidenced a high actual person–job fit but a low perceived person–job fit in the aeronautical or aerospace engineering programs and a low actual person–job fit and perceived person–job fit in the remaining ones. Results suggested that students' attraction to pursuing a career in aviation might be negatively affected but, if starting out in a manufacturing industry, students were likely to perform above their initial expectations.